Effects of long-term exposure to major outdoor air pollutants for the risk of chronic inflammatory airway diseases in adults with potential interaction detection in Taiwan Biobank. (1st November 2022) - Chang, Chin-Kuo; Lin, Yu-Kai; Lin, Chien-Wei; Su, Ming-Wei; Chu, Hou-Wei; Wu, Chih-Da; Zeng, Yu-Ting; Chang, Bao-Luen
Abstract: Background: Research on the association between chronic inflammatory airway diseases (CIADs), defined as asthma, chronic obstructive pulmonary disease, and impaired lung function, and long-term exposure of outdoor air pollutants for adults has been scarce. Research question: Effects of long-term exposure for outdoor air pollutants to the risk of CIADs in adults. Materials and methods: Applying data from Taiwan Biobank, 10-year accumulative exposure of major outdoor air pollutants, PM2.5, PM10, NO2, SO2, CO, and O3, was estimated by Kriging's interpolation, based on 76 nationwide air pollution monitoring stations linked to residency information at township or district level at baseline interview for volunteered community participants older than 30 years old. Eligible cases and randomly selected healthy controls constructed a nested case-control study with frequency matching on age and sex at a ratio of 1:4. We adopted logistic regression to estimate odds ratios (ORs) and 95% confidence intervals (CIs) of outdoor air pollutants to the risk of CIADs for univariable and multivariable analyses. For detecting potential interactions among critical covariates, we used the generalized multifactor dimensionality reduction method. Results: Higher 10-year cumulative exposure of NO2 and SO2 put people at a significantly elevated relative risk of CIADs after confounding control, showing adjusted ORs of 1.07 (95% CI: 1.01, 1.14) for NO2 and 1.23 (95% CI: 1.15, 1.31) for SO2 for each increment of standard deviation. Furthermore, a significant synergistic interaction ( P -value < 0.01 for interaction term) between PM10 and CO in tertiles was detected with an adjusted OR of 5.01 (95% CI: 2.95, 8.49) for the highest tertiles of PM10 and CO combined, relative to the group of lowest tertile combination. Conclusion: Our outcomes contributed to a more profound understanding on the effects of long-term exposure of air pollutants to CIADs in etiology, highlighting a synergistic interaction between PM10 and CO. Highlights: Studies on chronic inflammatory airway diseases for long-term outdoor air pollutant exposure in adults were scarce. Ten-year accumulative exposures of major outdoor air pollutants were estimated by Kriging's method in Taiwan Biobank. Long-term exposures of NO2 and SO2 were found significant to increase risks of chronic inflammatory airway diseases. A synergistic interaction between PM10 and CO was detected, suggesting a mechanism in pathogenesis.